Drug Addiction: From Neuroscience to Ethics - Farisco, Michele; Evers, Kathinka; Changeux, Jean-Pierre (Frontiers in Psychiatry, 2018)
In the present paper we suggest a potential new ethical analysis of addiction focusing on the relationship between aware and unaware processings in the brain, i.e. on what is consciously and what is non-consciously perceived by the individual. We take the case of the opioids epidemics to argue that a consideration of both aware and unaware processings provides a more comprehensive ethical framework to discuss the ethical issues raised by addiction. Finally, our hypothesis is that in addition to identified Central Nervous System’s neuronal/neurochemical factors contributing to addictive dynamics, the socio-economic status, i.e. the individual background, plays a causal role through epigenetic processes, originating the need for additional reward in the brain. This provides a strong base for a socio-political form of responsibility for preventing and managing addiction crisis.